The Effects of Night Work on Nurses and an Analysis of Countermeasures. (September 2016) - Costedoat, Gregory; Nathan-Roberts, Dan
Nurses are expected to work a variety of different shifts throughout their careers, including traditional day shifts, night shifts, and swing shifts. Research suggests that night shifts can have potentially adverse effects on a worker's perceptual and motor capacities, circadian rhythm, and ability to function the following day. Due to the critical role that nurses play in the health care delivery system, it is worth exploring options that serve to mitigate the aforementioned consequences associated with working at night. A number of potential countermeasures are explored, including slow shift rotations, naps, melatonin supplements, and caffeine. It is concluded that implementing slow rotating shifts and allowing time for a nap during the first night shift of a new rotation could have the largest impact on maximizing worker and patient safety.